ASPECTS TO CONSIDER IN DEVELOPING INTERCULTURAL COMPETENCE - Kurbanova Feruza Komiljanovna (Galaxy International Interdisciplinary Research Journal, 2022)
In this article we aim to discuss information about intercultural competence. In this article there are given the basic aspects of intercultural competence and their peculiarities, ideas on how to develop, what issues affect this process.